INTRODUCTION What is Service Learning? - Hironimus-Wendt, R.J. (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
It is important up front to dispel a common myth about service learning: service learning is not volunteerism (i.e., it is not simply service). Service learning is a structured learning opportunity that utilizes the community-at-large to support the theoretical knowledge being developed in the classroom and through textual readings. Because it is based upon experiential learning, the knowledge and skills learned in service learning represent a foundation for "life-long learning." In our course, we will focus primarily on in school and after school tutoring and mentoring programs.